Replacement of the Genomic Scaffold Improves the Replication Efficiency of Synthetic Klebsiella Phages - Baykov, Ivan K.; Kurchenko, Olga M.; Mikhaylova, Ekaterina E.; Miroshnikova, Anna V.; Morozova, Vera V.; Khlebnikova, Marianna I.; Tikunov, Artem Yu; Kozlova, Yuliya N.; Tikunova, Nina V. (International journal of molecular sciences, 2025)
In this study, the impact of the genomic scaffold on the properties of bacteriophages was investigated by swapping the genomic scaffolds surrounding the tailspike genes between two Przondovirus phages, KP192 and KP195, which infect Klebsiella pneumoniae with different capsular types. A yeast-based transformation-associated recombination cloning technique and subsequent “rebooting” of synthetic phage genomes in bacteria were used to construct the phages. Using Klebsiella strains with K2, K64, and KL111 capsular types, it was shown that the capsular specificity of the synthetic phages is fully consistent with that of the tailspike proteins (tsp). However, the efficiency of plating and the lytic efficiency of these phages strongly depended on the genomic scaffold used and the Klebsiella strain used. Synthetic phages with swapped genomic scaffolds demonstrated superior reproduction efficiency using a number of strains compared to wild-type phages, indicating that some elements of the swapped genomic scaffold enhance phage replication efficiency, presumably by blocking some of the host anti-phage defense systems. Our findings demonstrate that even in the case of closely related phages, the selection of the genomic scaffold used for tsp gene transplantation can have a profound impact on the efficiency of phage propagation on target bacterial strains.